Influencia de la fertilizacion en la cebolla cultivada en suelos afectados por sales - Morales, M.=700 1 Maestrey, A.; Galvez, V.; Vazquez, E.I.
(En, Es)
Ilus., 15 ref.
Keywords: ALLIUN CEPA; ABONOS NPK; SUELO SALINO; CUBA